Size And Interparticle Interaction Effects On Optical Properties Of Gold Nanoparticles Surface Plasmon Resonance Emission By Mnpbem Toolbox - Rahim, Siti Nur Shafiqa Abdul (2020)
Nowadays, gold nanoparticles have gained a great interest among researchers, owing to their fascinating optical properties which arise from the phenomenon of the surface plasmon resonance. The tunability of these properties makes gold nanoparticles attractive for many applications. By employing MNPBEM Toolbox, the optical properties of the gold nanoparticles have been studied. In order to verify the accuracy of this approach, a series of extinction spectra for a single spherical gold nanoparticle of different size had been simulated. Additionally, to make the simulation more realistic, the size effects had been taken into account. Next, the effect of the interparticle distance on the surface plasmon resonance had been elucidated, by categorizing it into two classes namely short-distance range and long-distance range. For the first range, the focus of this work was to scrutinize the validity of the well-known plasmon ruler equation when the nanostructure was transformed from dimer to linear chain. Concurrently, the objective for the long-distance range was to determine the interparticle distance at which the near field interaction of gold linear chains transits to the far field interaction. From the simulation results, it was observed that a single gold nanosphere had experienced the redshift and broadening of the resonance peak when the nanoparticle size was increased. The good agreement between the simulation results (obtained from this work) and the experimental results (obtained from the reported studies) corroborated the validity of this approach. Moreover, it was found that the plasmon ruler equation was size-dependent.